Child labor : an American history - Hindman, Hugh D. (Issues in work and human resources., 2002)
Despite its decline throughout the advanced industrial nations, child labor remains one of the major social, political, and economic concerns of modern times. This book considers the issue in three parts. The first section discusses child labor as a social and economic problem in America from an historical and theoretical perspective. The second part presents child labor as National Child Labor Committee investigators found it in major American industries and occupations, including coal mines, cotton textile mills, and sweatshops, in the early 1900s. Finally, the concluding section integrates these findings and attempts to apply them to child labor problems in America and the rest of the world today.